The Strategy of Ethics Education as a Means of Student Character Building: A Case Study at SMA Muhammadiyah 1 Metro - Hadi, Samsul; Sugiarti; Winarjo, Wahyudi (Journal of Strategy and Transformation in Educational Management, 2025)
The integration of character education in schools is very important to develop students' ethical (moral) values, despite facing challenges from family background and the influence of digital media, schools try to collaborate with parents in efforts to educate children at home and conduct digital literacy to strengthen ethical values. Good school programs can be carried out in order to form students' personal morals and ethics. This study uses a descriptive qualitative approach chosen because it describes the phenomenon in depth based on the views of participants. The purpose of this study is to describe the strategy of ethics education in shaping student character at SMA Muhammadiyah 1 Metro, which includes ethics education, factors of ethics formation, the role of Islamic religious education in shaping ethics, shaping children's mentality, educating student morals, and preparing superior generations. The results of this study show that ethics education is systematically integrated through religious activities (congregational prayer and tahfidz program), social activities (Friday clean and donation), and habituation of character values by teachers. The contribution of this research can have a positive impact on educators, educational institutions, and policy makers in preparing a superior generation with character.